2013
DOI: 10.1371/journal.pone.0057308
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Treatment of Adolescent Rats Causes Enduring Specific Memory Impairments and Alters Cortical Development and Function

Abstract: Antipsychotic drugs are increasingly used in children and adolescents to treat a variety of psychiatric disorders. However, little is known about the long-term effects of early life antipsychotic drug treatment. Most antipsychotic drugs are potent antagonists or partial agonists of dopamine D2 receptors; atypical antipsychotic drugs also antagonize type 2A serotonin receptors. Dopamine and serotonin regulate many neurodevelopmental processes. Thus, early life antipsychotic drug treatment can, potentially, pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 109 publications
(142 reference statements)
6
81
2
Order By: Relevance
“…Milstein and colleagues (Milstein et al 2013) investigated the effects of early Olanzapine treatment on locomotor activity in adulthood, with no changes to numerous parameters of the open-field test observed. Similarly, the present study found increases in the activity levels of Olanzapine-treated animals in the FS test but not in the Open-Field/Holeboard test, potentially due to the increased stress levels induced by the FS testing procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Milstein and colleagues (Milstein et al 2013) investigated the effects of early Olanzapine treatment on locomotor activity in adulthood, with no changes to numerous parameters of the open-field test observed. Similarly, the present study found increases in the activity levels of Olanzapine-treated animals in the FS test but not in the Open-Field/Holeboard test, potentially due to the increased stress levels induced by the FS testing procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although current clinical research into the use of APDs in the adolescent population over both a short term period of between 1-2 months, and longer-term period of up to 6 months has found some benefits in the treatment of some mental illness symptomology (Stigler et al 2004; Kumra et al 2008;Zuddas et al 2011), there is limited data on the potential for longterm alterations to adult behaviours (Milstein et al 2013;Shu et al 2014;Varela et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it remains plausible that ultra-structural changes such as alterations in the dendritic spines can occur (Frost et al 2010;Milstein et al 2013).…”
Section: Brain Structural Outcome and Neural Metabolism With Chronicmentioning
confidence: 99%
“…A few preclinical studies over the past five years have also started to examine long-term neurobiological consequences of adolescent treatment with atypical APDs (De Santis et al 2016;Milstein et al 2013;Qiao et al 2013;Vinish et al 2013). For example, adolescent treatment with olanzapine has been shown to induce long-term deficits in behaviour in adulthood, such as alterations in working memory, fear conditioning, reward behaviour (to amphetamine) and anxiety/depression-related behaviour, as well as changes in neurotransmission in the NAc, and dendritic spine pruning in other major brain regions (Brooks et al 2016;De Santis et al 2016;Milstein et al 2013;Xu et al 2015).…”
Section: Introductionmentioning
confidence: 99%